2005
DOI: 10.1007/s00013-005-1070-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonbranching weak and starshaped strong solutions for Hele-Shaw dynamics

Abstract: We consider multidimensional weak and strong Hele-Shaw dynamics (t) of an advancing/receding viscous fluid injected/removed through a single finite point into/from a bounded domain (0). A class of weak solutions is shown to preserve local uniqueness in both directions. Then we also consider strong solutions (t), and show that if (0) is starshaped with respect to a small ball centered on the point of injection, then the evolution (t) exists for all time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Following to [11] and [12] we rewrite the corresponding Hele-Shaw problem as a couple of two problems, namely, the time-independent Riemann-Hilbert problem for a doubly connected domain and an evolution problem reformulated as an abstract Cauchy-Kovalevsky problem. In contrast to the case of simply connected domain in our situation there is no explicit formula for the Riemann-Hilbert problem (see, e.g., [13]- [15], [16], cf., also [7]).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…Following to [11] and [12] we rewrite the corresponding Hele-Shaw problem as a couple of two problems, namely, the time-independent Riemann-Hilbert problem for a doubly connected domain and an evolution problem reformulated as an abstract Cauchy-Kovalevsky problem. In contrast to the case of simply connected domain in our situation there is no explicit formula for the Riemann-Hilbert problem (see, e.g., [13]- [15], [16], cf., also [7]).…”
Section: Introductionmentioning
confidence: 87%
“…The study of complex-analytic Hele-Shaw model going back to [5] and to [6] (cf. also the recent monograph [7]). This approach was applied to melting/freezing process in [8]- [10].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This occurs when a simply connected domain Ω(T ) for some 0 < T < ∞ can be obtained as a result of a strong simply connected dynamics Ω(t), or else, as a result of a weak dynamics G(t), where G(t) for t < T is multiply connected with some holes to be filled in as t → T − . In [32] it was shown that for a simply connected initial domain the classical solution does not branch backward in time (if it exists).…”
Section: Holds For Any Function H Which Is Harmonic In An Open Set Comentioning
confidence: 98%
“…These statements are based on the known regularity results for the obstacle problem [76], [77], [80], [79], [193], [431] combined with geometric results (relevant parts of Theorem 4.7.2 remain true [243]). Under certain assumptions, like strong starlikeness of the initial domain, it is possible even to prove the existence globally in time in the well-posed time direction (injection) [248]. Compare also [100], [154].…”
Section: Multidimensional Hele-shaw Flow and Other Generalizationsmentioning
confidence: 99%